K-Ar dating of young volcanic rocks - Damon, Paul E.; Shafiqullah, Muhammad (University of Arizona. Department of Geosciences., 1991)
Potassium-Argon (K-Ar) age dates were determined for forty-two young geologic samples by the Laboratory of Isotope Geochemistry, Department of Geosciences, in the period February 1, 1986 to June 30, 1989. Under the terms of Department of Energy Grant No. FG07-86ID12622, The University of Arizona was to provide state-of-the-art K-Ar age dating services, including sample preparation, analytical procedures, and computations, for forty-two young geologic samples submitted by DOE geothermal researchers. We billed only for forty samples. Age dates were determined for geologic samples from five regions with geothermal potential: the Cascade Mountains (Oregon); the Cascade Mountains (Washington); Ascension Island, South Atlantic Ocean; Cerro Prieto, Mexico; and Las Azufres, Mexico. The ages determined varied from 5.92 m.a. to 0.62 m.a. The integration of K-Ar dates with geologic data and the interpretation in terms of geologic and geothermal significance has been reported separately by the various DOE geothermal researchers. Table 1 presents a detailed listing of all samples dated, general sample location, researcher, researcher's organization, rock type, age, and probable error (1 standard deviation). Additional details regarding the geologic samples may be obtained from the respective geothermal researcher. 1 tab.